(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
Color adjectives constitute a significant lexical-semantic group within the system of adjectives and play a crucial role in structuring human perception, cognition, and linguistic categorization of reality. This article explores the place of color adjectives among parts of speech and their functional, semantic, and cognitive roles within the language system. Drawing on theoretical linguistics, cognitive semantics, and cross-linguistic studies, the paper examines the grammatical status of color adjectives, their interaction with other lexical categories, and their contribution to meaning-making processes. The study employs qualitative linguistic analysis, comparative methods, and discourse-based interpretation. The findings demonstrate that color adjectives are not merely descriptive units but multifunctional linguistic elements that reflect cultural values, conceptual structures, and systemic organization of language.